Let $P_n(x)$ be the $n$-th degree Legendre polynomial. Let $k$ be a nonnegative integer less than or equal to both $n,m$. How to prove that $$ \int_{-1}^1 (1-x^2)^k D^kP_n(x) D^kP_m(x)\,dx = \frac{2(n+k)!}{(n-k)!(2n+1)}\delta_{mn}, $$ where $D^k$ stands for derivative of order $k$, and $\delta_{mn}$ stands for Kronecker delta.

I think somehow we will use the orthogonality of $P_n, P_m$ and the norm of $P_n$, but I don't see how.

  • 1
    $\begingroup$ One way is to introduce $f_{n,k}(x) = (1-x^2)^{k/2} D^kP_n(x)$, and to prove by induction on $k$ that $f_{n,k}$ satisfy a certain 2nd order ODE. This makes them eigenfunctions of a differential operator for different eigenvalues, hence orthogonal. $\endgroup$
    – user147263
    Jun 13 '14 at 5:39

Let $I(k,n,m)$ be the considered integral.

(1) Since $\deg P_n=n$, we see immediately that $I(k,n,m)=0$ if $k>n$ or $k>m$.

(2) Since $I(k,n,m)=I(k,m,n)$, we see that the remaining case to be considered is $0\leq m\leq n$.

(3) Assume that $0\leq m\leq n$. Noting that $-1$ and $1$ are multiple zeros of $(x^2-1)^kD^kP_m$ of multiplicity $k$, we obtain by using k-successive integrations by parts $$ I(k,n,m)=\int_{-1}^1P_n(x)D^k\left((x^2-1)^kD^{k}P_m(x)\right)dx $$

  • The polynomial $Q(x)=D^k\left((x^2-1)^kD^{k}P_m(x)\right)$ has degree $m$. So, if $m<n$ we obtain $I(k,n,m)=0$.
  • The remaining case is when $m=n$. Here $\deg Q=n$. Recalling that the leading coefficient of $P_n$ is $a_n=\frac{1}{2^n}\binom{2n}{n}$ we see that $P_n(x)=a_n(x^n+R_{n-1})$ with $\deg R_{n-1}<n$. Thus $$ \eqalign{ Q(x)&=D^k\left((x^2-1)^kD^{k}P_n(x)\right)\cr &=a_nD^k\left((x^2-1)^k\frac{n!}{(n-k)!}(x^{n-k}+R_{n-1}^{(k)})\right)\cr &=a_n\frac{n!}{(n-k)!}D^k\left( x^{n+k}+S(x)\right)\quad\hbox{with $\deg S<n+k$}\cr &=a_n\frac{n!}{(n-k)!} \frac{(n+k)}{n!}(x^n+T(x))\quad\hbox{with $\deg T<n$}\cr &=a_n \frac{ (n+k)!}{(n-k)!} x^n+\hbox{terms of degree $<n$}\cr &=\frac{ (n+k)!}{(n-k)!} P_n+\hbox{terms of degree $<n$} } $$ It follows using orthogonality $$ I(k,n,n)=\frac{ (n+k)!}{(n-k)!} \int_{-1}^1 P_n^2(x)dx= \frac{ (n+k)!}{(n-k)!}\frac{2}{2n+1} $$ since $\Vert P_n\Vert^2=\frac{2}{2n+1}$.

As a conclusion, the only cases where $I(k,n,m)$ is different from $0$ is when $n=m$ and $0\leq k\leq n$, and in this case $$ I(k,n,n)=\frac{ (n+k)!}{(n-k)!}\frac{2}{2n+1}. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.